MODEL PEMBELAJARAN RECIPROCAL TEACHING KAITANNYA DENGAN KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA - Suparni Suparni (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2016)
To achieve the learning objectives expected, a teacher should be able to choose and use a learning model, because learning model will affect the learning process and student mathematical communication. In reciprocal teaching learning model there are four activities, namely: predicting, summarizing, asking questions, and explain again. This fourth activities undertaken by the students after the teacher show them how to predict, summarize, make inquiries and explain. This learning model is very well suited to improve student’s mathematics communication because students can interact direcltly without any embarrassment to his friends so that they can solve problems in complex because the student will share his ideas and discussing in group to solve the problem by connecting to every asped of it, can connect matter with other matter and the real world.